2014
DOI: 10.1093/nar/gku565
|View full text |Cite
|
Sign up to set email alerts
|

Human ISWI complexes are targeted by SMARCA5 ATPase and SLIDE domains to help resolve lesion-stalled transcription

Abstract: Chromatin compaction of deoxyribonucleic acid (DNA) presents a major challenge to the detection and removal of DNA damage. Helix-distorting DNA lesions that block transcription are specifically repaired by transcription-coupled nucleotide excision repair, which is initiated by binding of the CSB protein to lesion-stalled RNA polymerase II. Using live cell imaging, we identify a novel function for two distinct mammalian ISWI adenosine triphosphate (ATP)-dependent chromatin remodeling complexes in resolving lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 76 publications
(106 reference statements)
2
59
0
Order By: Relevance
“…Although BRG1 was implicated in mammalian NER23, we could not detect its accumulation at DNA damage sites. However, consistent with previous reports2635, we could detect ACF1 and SNF2H accumulation at ultraviolet-damaged sites (Fig. 7a).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Although BRG1 was implicated in mammalian NER23, we could not detect its accumulation at DNA damage sites. However, consistent with previous reports2635, we could detect ACF1 and SNF2H accumulation at ultraviolet-damaged sites (Fig. 7a).…”
Section: Resultssupporting
confidence: 93%
“…Only about 30% of HBO1 protein was detected after 6 h of treatment with α-amanitin or TSA. Therefore, it is possible that at least part of the reduced SNF2H recruitment observed in previous reports26 may be due to decreased HBO1 expression.…”
Section: Resultsmentioning
confidence: 88%
“…Recent studies have also indicated that DSBs may be processed in a CSB-facilitated mechanism that involves active transcription 29 . We report herein that RNAPII inhibition similarly impairs CSB recruitment to angelicin monoadducts, a phenomenon that might be predicted for these bulky modifications, and is generally consistent with prior experiments demonstrating that α-amanitin reduces TC-NER protein (e.g., CSB and SMARCA5) accumulation at UV photoproducts 55 . Notably, we did not observe an effect of α-amanitin treatment on the early recruitment phase of CSB to sites of oxidative DNA damage, although there was a slight, albeit significant, reduction in total protein accumulation/retention after 20 min.…”
Section: Discussionsupporting
confidence: 91%
“…As reported in other systems, SMARCA5 and SMARCD1 proteins were upregulated (Figure 4A) after inhibition of miR-99a/100 [21, 30]. Since SMARCA5 is known to be rapidly recruited at DNA damage sites in the nucleus [33], we measured post-radiation nuclear SMARCA5 and SMARCD1 accumulation in CB cells, using immunofluorescence. Both proteins reached their highest nuclear levels after 3 minutes and began to decline after 5 min (Supplementary Figure S2A).…”
Section: Resultsmentioning
confidence: 61%